Pharmacist's Demand for Optimal Primary Care Service Delivery in a Community Pharmacy: The OPTiPharm Study. (December 2017) - Munger, Mark A.; Walsh, Michael; Godin, Jon; Feehan, Michael
Background: The US population continues to expand providing the need for primary health care services. Community pharmacies integrated with medicine may provide greater access while providing high quality care.Objective: To gauge pharmacists' demand for primary health care services delivered through community pharmacies.Methods: An online survey was administered to determine community pharmacists' preferences for varying primary care services that could be offered in the community pharmacy setting. A Discrete Choice Experiment was employed to show pharmacists competing scenarios with varied primary care service offerings in the community pharmacy setting. Attributes evaluated were operation hours, service provider, medical records, service logistics, physical examinations, point-of-care diagnostic testing, preventative care, and drug prescribing. Respondents chose the scenario most likely to induce switching employment from base pharmacy to one providing advanced services.Results: The optimal service delivery model from 291 community pharmacists comprised: inclusion of patient prescriptions and health information into the patient's medical record; provision of point of care testing and vital sign, including blood pressure, heart rate and breathing rate, and blood sugar and cholesterol measurement; and pharmacists prescribing (under physician oversight). Pharmacists were 4 times more likely to switch employment from their current pharmacy to their choice for advanced pharmacy services. Pharmacist demand was highest among those with a PharmD, less experience, working >40 hours per week, and in rural areas.Conclusions: This study provides empirical support for the model of pharmacists playing a greater role in the provision of primary care health services through community pharmacy settings.